Peran Keluarga Dalam Mencegah Tindakan Bunuh Diri Menurut Ensiklik Evangelium Vitae - Talaud, Fransiskus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2024)
Human life is a gift from God that must be cherished and protected from the moment of conception until natural death. Therefore, every family member is obliged to respect and care for life in all its forms, including efforts to prevent actions that devaluate life, such as suicide. The importance of the family’s role in protecting and nurturing life led Pope John Paul II, in the Encyclical Evangelium Vitae, to describe the family as “the sanctuary of life.” This means that the family is the first environment where the values of life and human dignity are instilled. The research aims, first, to provide Catholics with an understanding of the Church’s view regarding the importance role of the family in protecting and respecting human life. Second, the author wants to highlight the values and principles taught by the Church to guide families in creating an environment that supports life, as well as preventing actions that threaten life, such as suicide.